Electrochemical Deposition of Porous Cobalt Oxide Films on AISI 304 Type Steel - Ieva KELPŠAITĖ; Jonas BALTRUŠAITIS; Eugenijus VALATKA (Medžiagotyra, 2011)
Cobalt hydroxide films on AISI 304 stainless steel were prepared using the electrochemical deposition from neutral cobalt acetate solutions under galvanostatic conditions. The obtained films were characterized using X-ray diffraction, X-ray photoelectron spectroscopy, scanning electron microscopy and thermal analysis. It was established that as-deposited films consisted of α-modification with intercalated CH3COO- ions. The lamellar morphology of cobalt hydroxide film was retained in Co3O4 films obtained after the initial cobalt hydroxide film thermal treatment at 673 K. Electrochemical oxidation of as-deposited hydroxide films led to the formation of black oxohydroxide film, CoO(OH). http://dx.doi.org/10.5755/j01.ms.17.3.586